2011
DOI: 10.1371/journal.pone.0026753
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-MET Induces a Stem-Like Phenotype in Human Prostate Cancer

Abstract: Prostate cancer consists of secretory cells and a population of immature cells. The function of immature cells and their mutual relation with secretory cells are still poorly understood. Immature cells either have a hierarchical relation to secretory cells (stem cell model) or represent an inducible population emerging upon appropriate stimulation of differentiated cells. Hepatocyte Growth Factor (HGF) receptor c-MET is specifically expressed in immature prostate cells. Our objective is to determine the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…Peak calling by the model-based analysis for (-1 kb to +1 kb; -2 kb to +2 kb; -3 kb to +3 kb of TSSs); downstream elements (-1 kb to +1 kb; -2 kb to +2 kb; -3 kb to +3 kb of transcription stop sites); gene body ( 5′UTR, 3′UTR the strongest correlation in both the TCGA and MSKCC data sets, which may in part reflect the reported NOTCH regulation of SOX9 expression (29)(30)(31). The correlation with MAPK signaling may also reflect the reported SOX9 induction through activation of receptor tyrosine kinases, including FGFRs and MET (16,32).…”
Section: Sox9-binding Sites Identified By Chip-seq In Tmprss2:erg Fusmentioning
confidence: 83%
“…Peak calling by the model-based analysis for (-1 kb to +1 kb; -2 kb to +2 kb; -3 kb to +3 kb of TSSs); downstream elements (-1 kb to +1 kb; -2 kb to +2 kb; -3 kb to +3 kb of transcription stop sites); gene body ( 5′UTR, 3′UTR the strongest correlation in both the TCGA and MSKCC data sets, which may in part reflect the reported NOTCH regulation of SOX9 expression (29)(30)(31). The correlation with MAPK signaling may also reflect the reported SOX9 induction through activation of receptor tyrosine kinases, including FGFRs and MET (16,32).…”
Section: Sox9-binding Sites Identified By Chip-seq In Tmprss2:erg Fusmentioning
confidence: 83%
“…23 The inhibition of c-Met/hepatocyte growth factor (HGF) signaling was previously shown to decrease the growth and metastasis formation in melanoma. 24 Its activation was recognized to induce a stem-like phenotype in prostate cancer 25,26 and support stem-like phenotype in glioblastoma. 27 Therefore, we decided to test whether the targeting of this signaling axis in combination with the cytotoxic treatment resulted in a long-term anti-tumor effect.…”
Section: Introductionmentioning
confidence: 99%
“…Xenograft and in vitro data showed that MET expression increases following androgen deprivation (10,11). HGF further induces cell invasion associated with stem cell features (12). In these models, MET knockdown leads to inhibited growth (13,14).…”
Section: Introductionmentioning
confidence: 99%